Pre-diagnostic telomere length and colorectal cancer risk. (April 2022) - Yang, Keming; Prescott, Jennifer; Hazra, Aditi; Meyerhardt, Jeffrey A.; Zhang, Xuehong; De Vivo, Immaculata; Chan, Andrew T.; Du, Mengmeng; Giovannucci, Edward L.; Nan, Hongmei
Abstract: Background: Progressive telomere shortening may be related to genomic instability and carcinogenesis. Prospective evidence relating telomere length (TL) with colorectal cancer (CRC) risk has been limited and inconsistent. Methods: We examined the association between pre-diagnostic peripheral blood leukocyte TL and CRC risk in two matched case-control studies nested within the Nurses' Health Study (NHS) and the Health Professionals Follow-Up Study (HPFS). Relative leukocyte TL was measured using qPCR among 356 incident CRC cases and 801 controls (NHS: 186/465, HPFS: 170/336). Results: We did not find a significant association between pre-diagnostic TL and CRC risk [in all participants, multivariable-adjusted odds ratio (OR) (95% CI) for TL Quartile 1 (shortest) vs. Quartile 4 (longest) = 1.36 (0.85, 2.17), P-trend = 0.27; OR (95% CI) per 1 SD decrease in TL = 1.12 (0.92, 1.36)]. Conclusions: Our prospective analysis did not support a significant association between pre-diagnostic leukocyte TL and CRC risk. Highlights: Basic research has shown both telomere erosion and elongation may occur before/during tumorigenesis. Prospective epidemiologic evidence relating TL and CRC risk has been limited and inconsistent. We examined the TL/CRC association using prospective data from two U.S. cohorts. Our study did not support TL as a strong predictor of CRC risk.